2022
DOI: 10.1002/ctd2.66
|View full text |Cite
|
Sign up to set email alerts
|

Combining antiviral drugs with BET inhibitors is beneficial in combatting SARS‐CoV‐2 infection

Abstract: The COVID‐19 pandemic caused by the novel coronavirus SARS‐CoV‐2 has resulted in more than 500 million cases and 6 million deaths. Several antiviral therapies and vaccines have been developed to mitigate the spread of this infection. However, new approaches are required to battle emerging SARS‐CoV‐2 variants containing mutations that can reduce the vaccines' efficacy. The use of a combination of antiviral drugs with inhibitors of mammalian target of rapamycin (mTOR) signalling pathways has emerged as one of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
(47 reference statements)
0
4
0
Order By: Relevance
“…For example, BET inhibitors, as described above, can be used to decrease ACE2 expression. 90 Nrf2 activators can increase levels of Nrf2 and can activate the expression of antiviral mediators. 91 PB125, an Nrf2 activator, is known to decrease expression of both ACE2 and TMPRSS2, thus inhibiting viral entry.…”
Section: Molecular Machineries As a Therapeutic Targetmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, BET inhibitors, as described above, can be used to decrease ACE2 expression. 90 Nrf2 activators can increase levels of Nrf2 and can activate the expression of antiviral mediators. 91 PB125, an Nrf2 activator, is known to decrease expression of both ACE2 and TMPRSS2, thus inhibiting viral entry.…”
Section: Molecular Machineries As a Therapeutic Targetmentioning
confidence: 99%
“…Understanding of transcriptional regulation of ACE2 receptors has also helped in the determination of new therapeutic targets. For example, BET inhibitors, as described above, can be used to decrease ACE2 expression 90 . Nrf2 activators can increase levels of Nrf2 and can activate the expression of antiviral mediators 91 .…”
Section: Molecular Machineries As a Therapeutic Targetmentioning
confidence: 99%
“…BETs are known to mediate inflammatory and immune responses to viral infection in general [4] and regulate COVID-19 mediated cytokine storm and cardiac damage [33] . Multiple studies have described the reduction in SARS-CoV-2 replication and infection when the acetyllysine binding activity of BET BDs is blocked by the BET inhibitors, including JQ1, OTX015, ABBV-744, INCB054329, SF2523 and Apabetalone (RVX-208), but only when these inhibitors were used hours or days before the virus is introduced [30] , [33] , [34] , [35] , [36] , [37] , [38] . BRD2, and to a lesser extent BRD4, is an important positive transcriptional regulator of the SARS-CoV-2 entry receptors, such as angiotensin-converting enzyme 2 (ACE2) [31] .…”
mentioning
confidence: 99%
“…We note that the ability of BET inhibitors to suppress proinflammatory cytokine expression may be desirable later in infection as Mills et al found that treatment with the BET inhibitor INCB054329 in mice blocked the expression of proinflammatory cytokines during LPS challenge associated with SARS-CoV-2 induced cardiac dysfunction [33] . Another BRD4 inhibitor, SF2523, combined with antiviral entry inhibitors required minimal doses to block SARS-CoV-2 replication and infection, highlighting a benefit of combinatorial inhibition approaches [37] , [38] .…”
mentioning
confidence: 99%